If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+4)=-6(3x-4)+6x
We move all terms to the left:
3(x+4)-(-6(3x-4)+6x)=0
We multiply parentheses
3x-(-6(3x-4)+6x)+12=0
We calculate terms in parentheses: -(-6(3x-4)+6x), so:We get rid of parentheses
-6(3x-4)+6x
We add all the numbers together, and all the variables
6x-6(3x-4)
We multiply parentheses
6x-18x+24
We add all the numbers together, and all the variables
-12x+24
Back to the equation:
-(-12x+24)
3x+12x-24+12=0
We add all the numbers together, and all the variables
15x-12=0
We move all terms containing x to the left, all other terms to the right
15x=12
x=12/15
x=4/5
| -8x+15-4=-3(4x-5) | | 8=-8u+4(u+3) | | -2(4x-13)-7=10 | | 20.67x=62.01 | | -5x+4=4x | | 25=v+10 | | 144+5x+6=180 | | 6x+12=18x+9 | | 5=1/4g+3 | | 7c+10=10+7c | | 14+2x=-5x-2+5x | | 115+x=21 | | (3x-12)=78 | | 106=10-6x | | 36+12x=16+8x | | 6x-38+6x-38=5x+8 | | 4/3b−14=15 | | 27-2x=20+5x | | –8–3k2=11 | | n4/2-3=13 | | 4(x+9)=15x-19 | | 6x10=-8 | | 63=7x+98 | | 3x+6=9x+30=90 | | 2x²+6x-1=x²+6x | | 2(6x-9)-6=-3-4(-3x+5) | | 2=t+5/3 | | 4b=-4b=8b | | 43 b−14=15 | | -4k=76 | | 4x+11=3x+1=180 | | 37=7-6z |